Assessing the Social Determinants of Health of Patients from a Student-Run Free Clinic to Improve Appointment Attendance Post COVID-19 - Kennedy Stoll; Morgan Black; Brett Hopf; Asael Nunez; Katherine Smeltzer; Robin Danek; Ellen Ireland; Eric Reyes (Journal of Student-Run Clinics, 2024)
Background: In clinics offering care to underserved and underinsured populations, patients who do not present for scheduled appointments (‘no-shows’) constitute a recurrent problem. As student clinicians, we are responsible for working to identify and mitigate contributing barriers to care. The Mollie Wheat Memorial Clinic (MWMC) conducted a qualitative study to better understand the demographics of the population served and evaluate their barriers to care.Methods: Patients who presented to MWMC (show) were surveyed about demographic information and barriers to care. Over the same time interval no-shows were contacted via phone for brief interviews detailing reasons for absence. A text message reminder system was first implemented for the May 14, 2022, clinic date, and a text message was sent to each patient 24 hours before his or her scheduled appointment. MWMC tracked changes in patient show/no-show rates following reminder implementation.Results: From January 1st, 2021 to December 31st, 2022, 60 “show” patients were surveyed. 43.64% of patients lived below the poverty line, 59.32% lacked health insurance, 83% owned a reliable car, and 90% felt confident in their ability to attend appointments. No-show rates before and after text message reminder implementation were not significantly different.Conclusion: Survey demographic data suggests that MWMC patients lack optimal healthcare because of financial reasons and do not struggle with transportation to the degree we expected. Despite text message reminders, no-show rates remained high. Based on these results, we have concluded mechanisms working for other clinics aren’t necessarily effective in free, rural-focused clinics such as MWMC. We have proposed further research in community settings such as food pantries as this could potentially reach patients who do not come to the clinic because of logistical or financial reasons.